PENERAPAN PROSEDUR TERAPI OKUPASI AKTIVITAS WAKTU LUANG UNTUK PERUBAHAN GEJALA HALUSINASI PENDENGARAN PADA PASIEN SKIZOFRENIA DI RUMAH SAKIT JIWA DR. AMINO GONDOHUTOMO PROVINSI JAWA TENGAH: APPLICATION OF OCCUPATIONAL THERAPY PROCEDURES LEASE TIME ACTIVITIES FOR CHANGING HEARING HALUMINATION SYMPTOMS IN SCHHIZOPRENIA PATIENTS IN A Mental Hospital DR. AMINO GONDOHUTOMO CENTRAL JAVA PROVINCE - Nanang Khosim Azhari; Kharisa Anggi (SEKOLAH TINGGI ILMU KESEHATAN KESDAM IV DIPONEGORO, 2019)
Schizophrenia is a disorder in a person with a state of being unable to think logically so that he cannot control his behavior and emotions. One of the positive symptoms of schizophrenia is hallucinations. Hallucinations occupied the highest number in 2018 as many as 5,339 people in RSJD Dr. Amino Gondhoutomo, Central Java Province. Hallucinations are the inability to distinguish between internal and external stimuli. One of the therapies for hallucinations is occupational therapy. Occupational therapy is an activity to correct abnormalities, maintain and improve the client's health status. The purpose of this case study is to describe the symptoms of hallucinations before and after being given occupational therapy for leisure activities. This type of research is descriptive with a case study approach. This study used 2 people with auditory hallucinations as subjects who were willing to be respondents. The results showed a decrease in the score of hallucinatory symptoms before and after being given occupational therapy for leisure activities to Mr. T from 13 to 4 and Br. R from 16 to 8. It can be concluded that the provision of occupational therapy for leisure activities has an effect on reducing hallucinatory symptoms experienced by schizophrenic patients with auditory hallucinations.